2019
DOI: 10.1002/ijc.32340
|View full text |Cite
|
Sign up to set email alerts
|

Cervical adenocarcinoma in situ: Human papillomavirus types and incidence trends in five states, 2008–2015

Abstract: Primary prevention through the use of human papillomavirus (HPV) vaccination is expected to impact both cervical intraepithelial neoplasia (CIN) and adenocarcinoma in situ (AIS). While CIN is well described, less is known about the epidemiology of AIS, a rare cervical precancer. We identified AIS and CIN grade 3 (CIN3) cases through population‐based surveillance, and analyzed data on HPV types and incidence trends overall, and among women screened for cervical cancer. From 2008 to 2015, 470 AIS and 6,587 CIN3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 50 publications
0
45
0
3
Order By: Relevance
“…Previous reports have suggested geographic differences in the HPV types in CIN. HPV52 was more common in Japan, whereas HPV58 was common in China and Korea . These types may be more common in East Asia than in Western and African countries .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous reports have suggested geographic differences in the HPV types in CIN. HPV52 was more common in Japan, whereas HPV58 was common in China and Korea . These types may be more common in East Asia than in Western and African countries .…”
Section: Discussionmentioning
confidence: 94%
“…Chao et al also demonstrated that HPV18 was rarer in VAIN3 than in CIN3. HPV18 preferentially induced AIS over CIN3, suggesting that HPV18 also rarely induces vaginal SCC.…”
Section: Discussionmentioning
confidence: 97%
“…Cervical cancer is one of the most prevalent tumors in women, especially in impoverished areas (1). For about 90% of patients, cervical cancer is avoidable with the proactive treatment of human papillomavirus (HPV, the leading cause of cervical cancer) vaccination (2). However, since there remains a long way to eliminate poverty, cervical cancer could be a significant health issue in the upcoming decades (3).…”
Section: Introductionmentioning
confidence: 99%
“…In the New Mexico HPV Pap Registry, which linked population‐based cancer registry and screening data, significant declines from 2007‐2014 among CIN grades 1‐3 were observed among women aged 15‐19 years and also among women with CIN2 aged 20‐24 years 17 . Findings from the CDC's Human Papillomavirus Vaccine Impact Monitoring Project conducted in 5 US catchment areas showed significant declines in CIN2+ from 2008‐2015 among screened women aged 18‐24 years, 7 and in adenocarcinoma in situ cases among women aged 21‐24 years 6 . In addition, this project found that the proportion of HPV 16, 18–positive CIN2+ cases declined from 2008‐2014, with larger decreases among vaccinated women and younger age groups.…”
Section: Discussionmentioning
confidence: 98%
“…Although coverage was low at first introduction, HPV vaccination coverage has increased; coverage of ≥1 dose of HPV vaccine among female adolescents aged 13‐17 years increased from 37% in 2008 to 73% in 2019 4,5 . The impact of HPV vaccine on cervical disease has been shown by decreasing incidence of cervical precancers and decreases in vaccine‐type HPV prevalence in cervical precancer lesions in young women 6‐8 . The HPV vaccine impact on invasive cervical cancer has not yet been fully shown because of the long duration for cancer development and a lower burden of invasive cervical cancer in younger women in whom HPV vaccination would have the most impact.…”
Section: Introductionmentioning
confidence: 99%